Decolourisation of triphenylmethane dyes by biogenically synthesised iron nanoparticles from fungal extract. Issue 1 (2nd January 2022) - Schuster, Simon; Su Yien Ting, Adeline
ABSTRACT: In this study, the extract from endophytic Fusarium proliferatum was used to synthesise iron nanoparticles (Fe-NPs). The properties of the biogenically synthesised Fe-NPs were then characterised by field emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDX) and Fourier transform infrared spectroscopy (FTIR). The efficacy of the synthesised Fe-NPs in decolourizing triphenylmethane dyes was evaluated. Results revealed that fungal extract from F. proliferatum was successfully used to synthesise Fe-NPs. The Fe-NPs produced were 20–50 nm in size, and consist of substantial elemental Fe content (14.83%). The FTIR spectra revealed the presence of amino acids and proteins on the surface of the Fe-NPs, confirming the biogenic synthesis of the Fe-NPs. When tested for decolourisation, the Fe-NPs were most effective in decolourising Methyl Violet (28.9%), followed by Crystal Violet (23.8%) and Malachite Green (18.3%). This study is the first few to report the biogenic synthesis of Fe-NPs using extracts from an endophytic Fusarium species and their corresponding dye decolourisation activities.